The Formulation of Credit Policy Models - Mehta, Dileep (Management Science, 1968)
This study undertakes to apply the statistical technique of sequential decision process to a specific range of problems of (trade) credit management. In particular, the study examines two problems: first, credit extension policy on a specific request or account; and second, construction of indices measuring the effectiveness of such a policy. The end goal is to establish a control system which has heretofore resisted analytical solution. Since management exercises its discretion primarily during the credit-extension phase, and since subsequent phases of credit policy are closely related to this particular phase, attention is focused on this aspect of credit policy. However, the analysis does not ignore other important aspects of credit policy, such as bad-debt level, length of the credit period, collection activities, and level of lost sales. The above situation is then reversed: indices in terms of bad-debt level, receivable level, etc., measure the impact of credit extension procedures on the subsequent phases of credit policy. The strength of the suggested approach lies in the logical relationship between the operating decision rules, that meaningfully take into account past experience, and the control indices. Thus it helps management in framing the optimal credit policy. The limitations of the study, such as the implied assumption of linearity of cost data and the neglect of cash discount policy or an integrated investment scheme, do not detract from the operational usefulness of the suggested approach.